2023
DOI: 10.1186/s12864-023-09382-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-149-5p on intramuscular fat deposition in pigs based on metabolomics and transcriptomics

Abstract: As one of the important traits in pig production, meat quality has important research significance and value. Intramuscular fat (IMF) content is one of the most important factors affecting pork quality. Many experimental studies have shown that IMF content is closely related to the flavor, tenderness, and juiciness of pork. Therefore, it is of great significance to study the mechanism of porcine IMF deposition. Previous research indicated that miR-149-5p promoted the proliferation of porcine intramuscular (IM)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The study revealed that miR-149-5p promoted the proliferation of porcine intramuscular preadipocytes while concurrently reducing their differentiation ability. Metabolomics analysis further demonstrated significant alterations in lipid, organic acid, and organic oxygen metabolites upon the overexpression of miR-149-5p in porcine intramuscular preadipocytes [ 80 ]. In a separate inquiry, an integrated analysis of liver metabolomics and transcriptomics was conducted to unveil oxidative stress in piglets affected by intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that miR-149-5p promoted the proliferation of porcine intramuscular preadipocytes while concurrently reducing their differentiation ability. Metabolomics analysis further demonstrated significant alterations in lipid, organic acid, and organic oxygen metabolites upon the overexpression of miR-149-5p in porcine intramuscular preadipocytes [ 80 ]. In a separate inquiry, an integrated analysis of liver metabolomics and transcriptomics was conducted to unveil oxidative stress in piglets affected by intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of meat is influenced by various factors, with intramuscular fat (IMF) content being the primary factor 1 . Previous studies have exhibited that a high IMF content is believed to promote sensory experience during consumption, as IMF positively influences the juiciness, palatability, and flavor of various types of meat 2 , 3 . For a prolonged duration, intensive selection for growth rate and lean meat percentage has significantly enhanced the economic advantages of lean pigs but resulted in a significant reduction in meat quality traits 4 .…”
Section: Introductionmentioning
confidence: 99%